Methodological Organization of the Theoretical Anatomy Class: Proposal Informed by Teaching Practice in Health Sciences - José Bailón-Mieles; Claudia Drogo (Journal of Education Method and Learning Strategy, 2026)
The teaching of Anatomy in Health Sciences continues to face the challenge of moving beyond pedagogical models focused solely on isolated morphological description, which may limit knowledge integration and its application to clinical reasoning. This article proposes a methodological framework for structuring theoretical sessions in Human Anatomy II, oriented toward strengthening basic-clinical correlation and fostering meaningful learning. A qualitative approach with a reflective-interpretative design was adopted, drawing on Schön’s reflective practice model to analize teaching experiences and didactic materials used in medical education. The resulting framework organizes the class session into three pedagogical phases (introduction, development, and conclusions) integrating strategies for cognitive activation, active retrieval of information, cognitive load regulation, and early clinical integration. The findings suggest that this methodological structure enhances the integrated understanding of anatomical knowledge and strengthens the early development of clinical reasoning, constituting a reproducible pedagogical framework for competency-based education in Health Sciences.